EFFECT OF SINTERING TEMPERATURE ON THE ROLLED COPPER-SHEATHED MONOFILAMENT MgB2 SUPERCONDUCTING WIRE - Herbirowo, Satrio; Imaduddin, Agung; Sofyan, Nofrijon; Yuwono, A.H (Teknologi Indonesia, 2017)
The manufacture of low temperature superconductor (LTS) MgB2 with relatively high critical temperature (Tc = 39K) wire fabricated by powder-in-tube (PIT) is a multi-step process. The main difficulty is that the value of Tc superconductor wire is determined by various factors. MgB2 superconductor has been developed for possible utilization in various practical applications, such as Magnetic Resonance Imaging. The fabrication process of 2 mm rolled-copper sheath monofilament superconductor MgB2 wire using mechanical deformation process, including rolling and drawing, has been carried out. Starting by inserting powders, containing nominal composition of MgB2 into Cu tube with inner ø of 4 mm and outer ø of 6 mm, then they were rolled and drawn into wires (ø 2 mm), subsequently. The process of copper tube rolling was subsequently repeated in order to obtain three samples using added 5% CNT and 10% CNT to the pure MgB2, then were heat-treated at 800°C for 2 hours respectively. The writers evaluated the doping effect of two types multiwall carbon nanotube (MWCNT) with different aspect ratios on MgB2/Cu monofilament wires. Surface morphology was analyzed with SEM, crystal structure of MgB2 with XRD, whereas temperature dependence resistivity with four-point probe Cryogenic Magnet. SEM-EDS images showed that without addition of CNT, the crystal of MgB2 form dispersed uniformly in wire, but when added with 5% and 10% of CNT, the particle dispersed morphology was observed due to substitution of atom C into atom B. In contrast with pure MgB2, however, the pores increased as the CNTs doped increased of up to 5 wt%, makes it hard to identify the critical temperature. The temperature dependence of resistivity results showed that the critical temperatures were detected and kept shifting toward high 40 K with the addition of 10 wt% CNT. XRD analysis showed that some Mg may react with CNT to form MgB4 and graphite. Mg may react with oxygen to form MgO because the Cu sheath is not fully sealed and vacumed.